CEA-FJSP: Carbon emission-aware flexible job-shop scheduling based on deep reinforcement learning - Wang, Shiyong; Li, Jiaxian; Tang, Hao; Wang, Juan (Frontiers in Environmental Science, 2022)
Currently, excessive carbon emission is causing visible damage to the ecosystem and will lead to long-term environmental degradation in the future. The manufacturing industry is one of the main contributors to the carbon emission problem. Therefore, the reduction of carbon emissions should be considered at all levels of production activities. In this paper, the carbon emission as a parvenu indicator is considered parallelly with the nobleman indicator, makespan, in the flexible job-shop scheduling problem. Firstly, the carbon emission is modeled based on the energy consumption of machine operation and the coolant treatment during the production process. Then, a deep reinforcement learning-based scheduling model is proposed to handle the carbon emission-aware flexible job-shop scheduling problem. The proposed model treats scheduling as a Markov decision process, where the scheduling agent and the scheduling environment interact repeatedly via states, actions, and rewards. Next, a deep neural network is employed to parameterize the scheduling policy. Then, the proximal policy optimization algorithm is conducted to drive the deep neural network to learn the objective-oriented optimal mapping from the states to the actions. The experimental results verify that the proposed deep reinforcement learning-based scheduling model has prominent optimization and generalization abilities. Moreover, the proposed model presents a nonlinear optimization effect over the weight combinations.